The seasonality and geographic dependence of ENSO impacts on U.S. surface ozone variability - Li Xu; Jin‐Yi Yu; Jordan L. Schnell; Michael J. Prather (Geophysical Research Letters)
Abstract We examine the impact of El Niño–Southern Oscillation (ENSO) on surface ozone abundance observed over the continental United States (U.S.) during 1993–2013. The monthly ozone decreases (increases) during El Niño (La Niña) years with amplitude up to 1.8 ppb per standard deviation of Niño 3.4 index. The largest ENSO influences occur over two southern U.S. regions during fall when the ENSO develops and over two western U.S. regions during the winter to spring after the ENSO decays. ENSO affects surface ozone via chemical processes during warm seasons in southern regions, where favorable meteorological conditions occur, but via dynamic transport during cold seasons in western regions, where the ENSO‐induced circulation variations are large. The geographic dependence and seasonality of the ENSO impacts imply that regulations regarding air quality and its exceedance need to be adjusted for different seasons and U.S. regions to account for the ENSO‐driven patterns in surface ozone.